Ameboma of the Ascending Colon - Loho, Lily Lucia; Meilany, Feronika Durry; Edwin, Leopold Jim (Gaceta Médica de Caracas, 2022)
Ameboma is a rare complication of the amebic colon. It is a tumor-like mass of granulation tissue and the diagnosis rests upon the demonstration of E. histolytica in the section obtained by biopsy. Ameboma of the colon occurs rarely and can present as a mass lesion simulating colonic cancer. We report a case of a 61-year-old woman presenting with abdominal pain and vomiting. On clinical and radiological examination, the diagnosis was ascending colon carcinoma.